ANALYSIS OF ADVERSE EVENT REPORTING AT ACCREDITED HOSPITALS - Tatiana Paula Miguelaci Ferezin; Daniele Ramos; Graziela Caldana; Carmen Silvia Gabriel; Andrea Bernardes (Universidade Federal do Paraná, 2017)
The objective was to analyze the reporting of adverse events at accredited hospitals in the interior of the state of São Paulo from the nursing team's perspective. Descriptive and cross-sectional survey with a quantitative approach, undertaken at three accredited hospitals in the interior of the state of São Paulo, with a sample of 61 nurses and 250 nursing technicians and auxiliary nurses. The data were collected between November 2014 and April 2015. It was demonstrated that 126 (75.4%) participants were knowledgeable to report adverse events, but only 109 (65.3%) reported being authorized to do so. The participants appointed the nurses as responsible for this action. In the total group of participants, 76 (45.5%) affirmed that the event reporting entails punitive measures for the professionals involved. Nevertheless, 62 (37,1%) did not highlight fear of punishment as a hindering factor. The institution should prioritize the learning and the safety culture, focused on improving the quality of care.